# Difference between revisions of "User talk:WikiSysop"

(→Case 1) |
(→Test Asymptote) |
||

Line 6: | Line 6: | ||

Test | Test | ||

==Test Asymptote== | ==Test Asymptote== | ||

+ | ===Test January 12th 2015=== | ||

+ | ====Case 1 modified==== | ||

+ | <asy> | ||

+ | size(0,300); | ||

+ | pair z1=(-1,0); | ||

+ | pair z2=(1,0); | ||

+ | real r=1.5; | ||

+ | path c1=circle(z1,r); | ||

+ | path c2=circle(z2,r); | ||

+ | fill(c1, lightred); | ||

+ | fill(c2, lightgreen); | ||

+ | picture intersection; | ||

+ | fill(intersection,c1,lightred+lightgreen); | ||

+ | clip(intersection,c2); | ||

+ | add(intersection); | ||

+ | draw(c1); | ||

+ | draw(c2); | ||

+ | label("$A$",z1); | ||

+ | label("$B$",z2); | ||

+ | path g=(0,-2)--(0,-0.25); | ||

+ | draw(Label("$A\cap B$",0),g,Arrow); | ||

+ | </asy> | ||

===Tests November 1th=== | ===Tests November 1th=== | ||

====Case 1 modified==== | ====Case 1 modified==== |

## Revision as of 13:46, 12 January 2015

## Contents

## Test Copy&Paste HTML

Test Test

## Test Asymptote

### Test January 12th 2015

#### Case 1 modified

### Tests November 1th

#### Case 1 modified

#### Case 1

### Tests November 17th

#### Case 1

### Tests November 4th

#### Case 1

#### Case 2

#### Case 3

### Tests October 27th

#### Case 1

#### Case 2

#### Case 3

#### Case 4

#### Case 5

[asy] pair A,B,C,X,Y,Z; A = (0,0); B = (1,0); C = (0.3,0.8); draw(A--B--C--A); X = (B+C)/2; Y = (A+C)/2; Z = (A+B)/2; draw(A--X, red); draw(B--Y,red); draw(C--Z,red); [/asy]

### Previous tests

## Test Cite Extension

Example: Cite-Extension

## Test MathJax

\begin{align} \dot{x} & = \sigma(y-x) \\ \dot{y} & = \rho x - y - xz \\ \dot{z} & = -\beta z + xy \end{align}

\[
\frac{1}{(\sqrt{\phi \sqrt{5}}-\phi) e^{\frac25 \pi}} =
1+\frac{e^{-2\pi}} {1+\frac{e^{-4\pi}} {1+\frac{e^{-6\pi}}
{1+\frac{e^{-8\pi}} {1+\ldots} } } }
\]

Some Text \( \frac{1}{(\sqrt{\phi \sqrt{5}}-\phi) e^{\frac25 \pi}} = 1+\frac{e^{-2\pi}} {1+\frac{e^{-4\pi}} {1+\frac{e^{-6\pi}} {1+\frac{e^{-8\pi}} {1+\ldots} } } } \)

Some Text
\[
\frac{1}{(\sqrt{\phi \sqrt{5}}-\phi) e^{\frac25 \pi}} =
1+\frac{e^{-2\pi}} {1+\frac{e^{-4\pi}} {1+\frac{e^{-6\pi}}
{1+\frac{e^{-8\pi}} {1+\ldots} } } }
\]

## Pages A-Z

Alphabetically ordered index of all pages

## Recent Changes

List of previous changes on EOM

.

**How to Cite This Entry:**

WikiSysop.

*Encyclopedia of Mathematics.*URL: http://www.encyclopediaofmath.org/index.php?title=WikiSysop&oldid=36237

Test January 12th 2015